2009
DOI: 10.1021/jf900591q
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fat Content on the Digestibility and Bioaccessibility of Cocoa Polyphenol by an in Vitro Digestion Model

Abstract: This work describes the applicability of an in vitro digestion model for the evaluation of the digestibility and bioaccessibility of cocoa polyphenols (procyanidins, phenolic acids, and flavones) and for the study of the food matrix effect in relation with the fat content. For this purpose, two cocoa samples, cocoa liquor ( approximately 50% fat content) and cocoa powder ( approximately 15% fat content), were used. The results showed an important increase of the concentration of procyanidin (monomers and dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(126 citation statements)
references
References 20 publications
11
104
0
3
Order By: Relevance
“…Enhancement of the digestibility of phenolic compounds in carob flour was evident in the presence of hazelnut oil rich in monounsaturated fatty acids (Ortega et al, 2009) similar to the positive effects of stearic acid and linoleic acid on punicalagin in this study.…”
Section: Changes In Total Anthocyanin Contents After Codigesting Pomesupporting
confidence: 82%
See 3 more Smart Citations
“…Enhancement of the digestibility of phenolic compounds in carob flour was evident in the presence of hazelnut oil rich in monounsaturated fatty acids (Ortega et al, 2009) similar to the positive effects of stearic acid and linoleic acid on punicalagin in this study.…”
Section: Changes In Total Anthocyanin Contents After Codigesting Pomesupporting
confidence: 82%
“…However, when jujube juice was ingested with whole milk, a significant reduction in the bioavailability of phenolics was reported and was related to the formation of complexes between proteins, fats, and phenolics during digestion. Some in vivo studies are available on the effect of oil or fats on the bioavailability of phenolic compounds (Lesser et al, 2004;Mullen et al, 2008;Zhang et al, 2012) but in vitro studies are very few (Ortega et al, 2009). …”
Section: Changes In Total Phenolic Contents After Codigesting Pomegramentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies, however, have observed a positive relationship. Ortega et al [49] found that higher fat content has a positive efect on the stability of cocoa polyphenols in an in vitro digestion model.…”
Section: Bioavailability and Bioaccessibilitymentioning
confidence: 99%